Mobile Education, Entertainment, and Exploration (MEEE) at heritage site - Kian, Lam Tan; Chen, Chen Kim Lim (2016)
Visitor would usually like to discover more about the attractions of a place before their physical visit. Nowadays, there are various applications available for the exploration of heritage sites. However, there is a need for applications that are more highly accessible with adventure and adaptive learning in a more entertaining manner on mobile platform.Mobile Education, Entertainment, and Exploration (MEEE) aims to allow users to have an immersive experience and first-touch sensation by roaming the 360◦ panoramic views of the cultural heritage sites together with acoustical heritage simulation and push notification on an interactive mobile device with trendy and stylish interfaces. Furthermore, anyone can acquire the knowledge of cultural heritage sites through a mobile game that integrates with the treasure hunt and the classical board games of monopoly.The mobile game is played with the customized avatars that are dressed in traditional garments.With these elements of audio, visual, accessibility and educational perspectives of the heritage sites are incorporated into a single application.The current implementation is based on the cultural heritage sites of Georgetown, Penang, Malaysia.Based on the survey and the comparison that were carried out, the outcome is very satisfying and the respondents were very pleased with the product of this research.With this application, local and international visitors can make the best ever decision to visit various heritage sites.